2011
DOI: 10.1007/s10620-011-1567-4
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Irritable Bowel Syndrome Based on Abdominal Pain/Discomfort Severity and Bowel Pattern

Abstract: INTRODUCTION IBS traditionally has been classified by stooling pattern (e.g., diarrhea-predominant). However, other patterns of symptoms have long been recognized, e.g., pain severity. Our objective was to examine the utility of subtyping women with IBS based on pain/discomfort severity as well as predominant bowel pattern. METHODS Women (n=166) with IBS completed interviews, questionnaires, and kept a diary for 28 days. Rome II questionnaire items eliciting past 3-month recall of hard and loose stools, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
2
23
0
1
Order By: Relevance
“…This partly explains the similarity in HR-QOL scores between the IBS-D, IBS-C, and IBS-M subtypes. However, the severity of abdominal pain or discomfort has a significant effect, larger than that of the subtype classification, on daily activities and beliefs about IBS, [52]. This supports the trend to include severity of IBS symptoms as an important dimension in therapy [53].…”
Section: Discussionmentioning
confidence: 62%
“…This partly explains the similarity in HR-QOL scores between the IBS-D, IBS-C, and IBS-M subtypes. However, the severity of abdominal pain or discomfort has a significant effect, larger than that of the subtype classification, on daily activities and beliefs about IBS, [52]. This supports the trend to include severity of IBS symptoms as an important dimension in therapy [53].…”
Section: Discussionmentioning
confidence: 62%
“…However, based on clinical experience, patients with IBS-M are more difficult to treat. Other published studies also supported clinical difference in the various IBS-subtypes, with patients with IBS-M subtype posing more difficulties in the management[64-66]. Hence, there is a good chance that the difference observed would be valid.…”
Section: Discussionmentioning
confidence: 77%
“…Heitkemper et al (27) have shown that the severity of abdominal pain/ discomfort has a stronger effect on the quality of life than altered bowel pattern in IBS female patients. Based on these findings the authors suggested that the categorization of IBS patients should include both abdominal pain/ discomfort severity and predominant bowel pattern.…”
Section: Discussionmentioning
confidence: 99%